School-Based Immunization, Access to Health Facilities, Breastfeeding, and Vitamin A Supplementation are Correlated with the Incidence of Measles: Ecological Study at the Provincial Level in Indonesia - Lindra Anggorowati; Lukman, Fauzi; Desty, Rani Tiara (Journal of Health Education, 2025)
Background: Measles remains a significant public health concern in Indonesia. The number of measles rose sharply from more than 4,800 cases in 2022 to over 10,600 cases in 2023. Objective: This study aimed to analyze the correlation between school-based immunization, access to health facilities, breastfeeding practices, vitamin A supplementation, integrated health post capacity, and the incidence of suspected measles cases at the provincial level in Indonesia. Methods: An ecological study design was applied using aggregated provincial level data from the Indonesia Health Profile 2024. Spearman’s rank correlation test was used to examine the correlation between some independent variables with measles incidence as dependent variable.  Result: In this study, several variables showed significant negative correlations with measles incidence of measles. Variables with significant correlations at p value<0.005 were number of children receiving school immunization (ρ =-0.930), number of regencies achieving 80% complete basic immunization (ρ=-0.730), number of students accessing health facilities (ρ=-0.798), number of babies receiving exclusive breastfeeding (ρ = -0.826) number of children receiving booster measles immunization (ρ=-0.659), number of babies receiving vitamin A (ρ=-0.505) and number of children under five receiving vitamin A (ρ=-0.477). Meanwhile, variables related to number of regencies receiving integrated health post training and activity levels 80% of active integrated health post did not show significant correlations with the incidence of measles (p value>0.05).  Conclusion: It can be concluded that school-based immunization, access to health facilities, breastfeeding, and vitamin A supplementation are correlated with the incidence of measles at the provincial level in Indonesia